A flow-induced structure-based kinetic energy harvester - Zhang, Guangcheng; Lin, Yueh-Jaw; Klumpner, Christian (2017)
In this paper, a strategy utilizing a pair of cylinders which are put on the both sides of the cantilever beam and perpendicular to the water flow direction to harvest the energy is demonstrated. The novel flow induced structure based energy harvester consists of a pair inducing objects (cylinders) and one L-type cantilever beam. Macro fiber composite (MFC) is attached at the fixed end of the cantilever beam to convert the kinetic energy into electric power. The structure could induce the vortex shedding from the upstream flow and harvest the energy from it. Compared with the former studies with one or series layout inducing objects, the proposed structure could both improve the power output of flow induced energy harvester and avoid the damage happening in complex working conditions. Analytical modelling and experiment methods are both utilized in the research to cross verify the results. The characteristics related with water flow speed and center distance variations between inducing objects are discussed in the paper as well. It is found that when the water flow speed is 0.2m/s and the center distance is 30mm, the output power is optimal of 0.16μW and the power density is 0.4mW/m2.